Evaluation of the effect of the supplementation of Agaricus brasiliensis mushroom in cytohematological, growth and stress parameters in Nile tilapias (Oreochromis iloticus) - Flávio F Silva; Alessandra Hugo de Souza; Wiliam CB Regis (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Currently, in fish farming, Nile tilapia farming is one of the most widespread types worldwide and is present on all continents. However, stressors are normal in intensive rearing systems, which triggers immune suppression leading to a higher chance of infection, with Aeromonas hydrophila being one of the main responsible for the frequent diseases. Inhibition of reproductive and growth performance are also frequently observed in these situations. Thus, it is more than necessary to develop efficient treatments not only against the immune damage generated by stress in fish but also to prevent oxidative stress itself as well as against its side effects related to physiology and infections. The mushroom Agaricus brasiliensis is widely recognized in the literature for its immunomodulatory and antioxidant effects, which makes it a potential supplement to counteract the effects of stress on intensive fish farming. In this study, we evaluated the effects of supplementation with the mushroom Agaricus brasiliensis through a randomized clinical trial regarding the immunological hematological variables in face of a normal situation and an induced stress situation as well as in the face of an immunological challenge by Aeromonas hydrophila. The mushroom proved to have a positive effect under the tested conditions, however, further studies will be necessary to determine its definitive effects.